Combining oligomer build-up with alanine scanning to determine the flocculation protein mutants for enhancing oligosaccharide binding. Issue 4 (4th March 2022) - Sun, Lu; Zhang, Chenhong; Chen, Jiemin; Zhao, Xinqing; Bai, Fengwu; Zhong, Shijun
ABSTRACT: Oligosaccharide binding on protein plays an important role in cellular signalling and recognition. Protein mutation can alter the binding strength and thus regulate the relevant processes. In this work, we investigated the interactions between the mannose oligosaccharides and the wild type and mutant forms of yeast flocculation protein Flo1p from Saccharomyces cerevisiae . The binding strength of an oligosaccharide chain was estimated using molecular dynamics simulation and MM/GBSA binding free energy calculation, via the build-up of oligosaccharide from monosaccharide to disaccharide, trisaccharide and tetrasaccharide. At the protein-disaccharide stage, several mutation positions were identified via alanine scanning mutagenesis, leading to nine mutants, from which two mutants Q117N and Q117R were selected with significantly stronger binding free energies relative to the wild type protein. Furthermore, the two mutants also show enhanced binding at the trisaccharide and tetrasaccharide stages. Conformational stability and shape change were analysed to help understand the protein-oligosaccharide interactions. This study also presented a computational example to estimate the oligosaccharide binding strength using its terminal sugar residues.